Zur Rolle empirischer Settings in mathematischen Wissensentwicklungsprozessen – eine exemplarische Untersuchung der digitalen Funktionenlupe (mathematica didactica, 2022)
This article presents a concept for the description of knowledge development processes on the basis of empirical objects in mathematics education. The so-called CSC-model uses terms and findings from the structuralistic theory-concept as well as from theories on beliefs about mathematics, on the context-related nature of learning processes and from cybernetic general model theory. The concept is then explicated in a case study on the digital function-microscope.